PRAKTIK ADOPSI PERTANIAN BERKELANJUTAN DI DESA BONDA RAYA, KABUPATEN BONE BOLANGO, GORONTALO - Irwan Bempah; Karlena Arsyad; M. Nur, Yuni Maulani (Universitas Veteran Bangun Nusantara, 2024)
Farmers’ low understanding of mitigating the adoption of sustainable agriculture has an impact on climate change in the agriculture sector. The objective of this research are to: determine corn farmers adoption of sustainable agricultural practices. The method used is quantitative research by conducting face-to-face interviews with farmers using a primary data questionnaire. The sampling consisted of 60 farmers. This research was conducted in Bonda Raya village, South Suwawa District, Bone Bolango Regency, Gorontalo Province. This research shows that the level of farmers adoption of sustainable agricultural knowledge is still relatively low. The role of extension workers can increase farmers awareness regarding climate change adaptation and mitigation efforts. The results of this research show that there is the highest value for soil processing (3,60) and the lowlest for the use of organic fertilizer (1,22). The average value sustainable agricultural practices is still low (2,06). The relationship betwen aspects of age, education and activeness in extension activites is significantly correlated with sustainable agricultural practices. Therefore, efforts are needed to increase farmers’ knowledge in reducing environmental impacts. By increasing farmer understanding and participation, adoption of more sustainable farming practices can also increase. Keywords: adoption of sustainable agriculture; climate change; mitigation.